The reproductive biology and ecology of Colchicum (Colchicaceae) in southern Africa - Kleizen, Ciara (Department of Biological Sciences, 2024)
The observation that many plants have developed sets of structural and functional adaptations that encourage visitation by pollinators has led biologists to define pollination syndromes. These syndromes reflect patterns of convergent evolution and serve to generate hypotheses about potential pollinators based on a plant's morphological characteristics (Faegri and van der Pijl, 1979; Johnson and Steiner, 2000).